LATAR BELAKANG KEMENANGAN JOE BIDEN DALAM PEMILU AMERIKA SERIKAT TAHUN 2020 - Muryantini, Sri; Fauziati, Adhelia Eka (Jurnal Paradigma, 2022)
The United States election in 2020 presents two tough opponents, namely Joe Biden and Donald Trump. Two candidates used their respective strategies to gain public support. The result of this election is the victory of Joe Biden who managed to get a landslide support than his opponent, Trump. This journal contains an analysis of Joe Biden’s victory in the 2020 United States election. The purposes of writing this journal is to find out the background of Joe Biden’s victory being elected President of the United States in the 2020 election. This study uses qualitative research methods. The theory used for this research is the theory of voter behavior. The results of this study indicate that Joe Biden’s victory is supported by three variables, namely identification of the party, utilization of developing issues and orientation to candidates so that many states in the United States choose him.